Market Integration Analysis of Big Red Chili in Lampung Province - Ebenezer Sinambela; Novi Rosanti; Ktut Murniati; Teguh Endaryanto (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
This study aims to determine the degree and behavior of red chili market integration within the red chili market region of Lampung Province through descriptive analysis with a quantitative approach using vector autoregression (VAR) method. This study uses secondary data provided by the Badan Pusat Statistik. There is a long-term relation between producer-level red chilli prices in Lampung, consumer-level big red chili prices in Bandar Lampung, consumer-level big red chili prices in South Sumatra, and consumer-level big red chili prices in Bengkulu. There is a one-way relation between producer-level red chili prices in Lampung and consumer-level big red chili prices in South Sumatra. There is also a one-way relationship between big red chili prices at the Bandar Lampung consumer level and big red chili prices at the Bengkulu and South Sumatra consumers levels.